VIBRATION CHARACTERISTICS ANALYSIS OF ROTOR-RUNNER SYSTEM UNDER FAULTY OIL COMPONENT - WU Jing; ZHANG LeiKe; WANG XueNi (Jixie qiangdu)
In the actual operation of bulb continuous unit, the rotor-runner system is easy to form friction fault between rotating parts and fixed parts allected by extermal incentives, which greatly affects the safe and stable operation of unit. Aimed at the problem of axial friction with fault receptor components, the unbalanced magnetic tension model under rotor composite eccentricity is conshructed, the vibration model of rotor-runner coupled bending torsional vibration with the excitation of multi-source, and its diferential motion equation are established. The dierence of vibration characteristics for converter system is studied and the nonlinear vibration characteristics of system in excitation curent, rotor and runner mass eccenticity are discussed. The results show that failure inereases the unsteady motion range of rotor and runner, causing the system to produce adverse vibration and occasion malfunetion. Meanwhile, the rotor under the same operating conditions and parameters shows a greater amplitude strength than the runmer, which should be more attention. With considering the torsional degrees of freedom, the rotor amplitude amplifies under mass eccentricity variations, resulting in the rub-impact malfunction. In addition, when the runner mass eccentricity is developed to a certain extent, the uncertain random hydraulic force at the blade will induce instability of system. The results can provide useful references for safe operation and stability analysis of bulb tubular unit.